Ἀνταλλάξιμα κτήρια, σιωπηλὲς κληρονομιές: Ἡ προσωρινὴ ἐγκατάσταση τῶν Μικρασιατῶν προσφύγων καὶ τὰ ἰσλαμικὰ τεμένη τῆς Θεσσαλονίκης - Καλλιμοπούλου, Ελένη; Πούλος, Παναγιώτης Κ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
At a transitional phase in the history of Thessaloniki, many public buildings were requisitioned to cover the urgent housing needs of the Asia Minor refugees who kept arriving to the city. The mosques of the city provided an instant means of shelter for refugees, as did the various Christian Orthodox churches that had been turned into mosques in Ottoman times and returned to the Greek community and to their initial usage following the incorporation of Thessaloniki in the Greek Kingdom. The changes in the usage of the buildings, which are documented in detail in the present article, played a part in the gradual obliteration from public space of the Muslim community and the recent Ottoman past, while they also attested and contributed to the refugee heritage of Thessaloniki. A crucial but little explored dimension of the aforementioned changes concerns the sonic mark of religious buildings on public space. The present study focuses on this historical moment of transition for Thessaloniki, through the history of sound in the everyday life of these buildings. Through archival sources, oral testimonies and references in the press, we seek to document and uncover the aural dimension, which forms also an important aspect in the history of the refugee settlement in Thessaloniki.